POTRET SELF-DISCLOSURE PADA DEWASA AWAL PENGGUNA SECOND ACCOUNT INSTAGRAM - Elizabeth Aprilia Caroline Ice (LPSDI Bina Patria, 2025)
Social media is the most popular among people especially in early adulthood and the increasing number of second account Instagram users do self-disclosure on their accounts because they have freedom in it without being judged by others. The lives of the three participants on their second Instagram accounts were explored qualitatively. Furthermore, the data from the participants were processed by transcendental phenomenology. The three participants are 18-year-old early adults who have and are active on second Instagram accounts. The findings in this study are that there are three themes that emerge in expressing themselves on their second account, namely in revealing their inner presentation to others, and reducing loneliness and for emotional release. The researcher hopes that in the future, early adult Instagram second account users will be more open and establish friendships that have closer trust in each other.